Prevention and control of COVID-19 epidemic among elderly people in China: challenge, practice and enlightenment - Xin GAO; Zhao-xue YIN; Jing WU (Editorial Office of Chinese Journal of Public Health, 2022)
Coronavirus disease 2019 (COVID-19) is the most widely spread epidemic in the past century, which poses a major threat to the safety and health of the whole population, especially to those of the elderly. China carried forward the traditional virtue of respecting and caring for the elderly in special times, adhered to unified leadership, joint prevention and control, society-wide prevention and control, and precise measure implementation for the elderly in the face of challenges such as poor physical and mental health, weak protection ability, and the "digital divide". During the period of COVID-19 prevention and control, China did its utmost to ensure life support and health service for old people. In this article, we summarized successful experience of COVID-19 epidemic prevention and control among the elderly in China and proposed some suggestions on improving health service system for elderly and constructing an elderly friendly society during the period of normalized COVID-19 epidemic prevention and control.